Measuring R&D effectiveness-II Robert Szakonyi offers a way of benchmarking your R&D department against the "average" department - Szakonyi, Robert
Compare your department's performance of ten basic activities with the performance of an "average" R&D department.
A new approach to measuring R&D effectiveness focuses on what R&D managers intuitively know is important. Ten R&D activities, from selecting the projects to linking R&D to business planning, are measured by identifying at which of six levels an R&D department is operating. The six levels are : (1) issue is not recognized; (2) initial efforts are made toward addressing issue; (3) right skills are in place; (4) appropriate methods are used; (5) responsibilities are clarified; and (6) continuous improvement is underway. With this approach, R&D managers can compare their department's performance in each activity against "an average" department, and identify those activities in which their department needs to improve.
Keywords: Effectiveness-R&D.